Full-Fat Black Soldier Fly Larvae Meal in Diet for Tambaqui, Colossoma macropomum: Digestibility, Growth Performance and Economic Analysis of Feeds - Driely Kathriny Monteiro dos Santos; Odair Rodrigues de Freitas; Cesar Augusto Oishi; Flávio Augusto Leão da Fonseca; Giuliana Parisi; Ligia Uribe Gonçalves (Animals, 2023)
Black soldier fly (BSF, Hermetia illucens) larvae is a prominent ingredient in aquafeeds due to its high protein and energy contents. This study evaluated the digestibility of full-fat BSF larvae meal (FF-BSFL) and its inclusion in diets for tambaqui, Colossoma macropomum. The apparent digestibility coefficient of FF-BSFL for protein and energy was around of 88%, corresponding to 33.55% and 21.61 MJ kg−1 of digestible protein and energy, respectively. For the feeding trial, tambaqui juveniles (53.23 ± 1.07 g) were distributed in a completely randomized experimental design (n = 4; 150 L tanks; 10 fish per tank). Fish were fed diets including 0%, 5.25%, 10.50%, and 15.75% FF-BSFL to apparent satiation for 60 days. Fish fed 10.50% FF-BSFL dietary inclusion showed higher weight gain, feed intake, final biomass, and relative growth rate. The 10.50% FF-BSFL diet presented the highest index of economic profitability. Weight gain fitted a third-degree equation and the optimum FF-BSFL inclusion level was estimated at 11.6%. However, FF-BSFL dietary inclusion up to 15.75% did not impair growth fish performance. FF-BSFL seems to be a promising source of protein and energy for omnivorous fish aquafeed.